2020
DOI: 10.3389/fphar.2020.554783
|View full text |Cite
|
Sign up to set email alerts
|

Functional Metabolomics Analysis Elucidating the Metabolic Biomarker and Key Pathway Change Associated With the Chronic Glomerulonephritis and Revealing Action Mechanism of Rhein

Abstract: Chronic glomerulonephritis (CGN) as the culprit of kidney failure can increase the mortality of critically ill patients and seriously threatens people's health all over the world. This study using metabolomics strategy is to reveal the potential therapeutic mechanism-related targets to evaluate the effects of rhein (RH) on CGN rats. Changes of serum metabolites and pathways were analyzed by non-targeted metabolomic method based on liquid chromatography-mass spectrometry (LC-MS) combined with ingenuity pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Rhein is considered to be a highly effective natural component for the treatment of kidney-related diseases. According to the analysis of Yu et al for the metabonomics, rhein could treat CGN by regulating or participating in the following six important metabolic pathways: phenylalanine, tyrosine and tryptophan biosynthesis, tricarboxylic acid cycle (TCA cycle), alanine, aspartate and glutamate metabolism, and arginine and proline metabolism [ 21 ]. According to a systematic review and meta-analysis, rhein has beneficial effects on diabetic nephropathy animal models by reducing levels of transforming growth factor- β (TGF- β 1), renal fibrosis, metabolism, and oxidative stress status [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rhein is considered to be a highly effective natural component for the treatment of kidney-related diseases. According to the analysis of Yu et al for the metabonomics, rhein could treat CGN by regulating or participating in the following six important metabolic pathways: phenylalanine, tyrosine and tryptophan biosynthesis, tricarboxylic acid cycle (TCA cycle), alanine, aspartate and glutamate metabolism, and arginine and proline metabolism [ 21 ]. According to a systematic review and meta-analysis, rhein has beneficial effects on diabetic nephropathy animal models by reducing levels of transforming growth factor- β (TGF- β 1), renal fibrosis, metabolism, and oxidative stress status [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…One such alternative treatment involves rhein (4,5‐dihydroxy‐9,10‐dioxoanthracene‐2‐carboxylic acid), a natural anthraquinone compound found in several herbal medicines, including rhubarb, aloe, and sennae leaf. Rhein has been recently reported to display therapeutic effects in several inflammatory conditions, such as skin wounding (W. Zhao et al, 2020), acute kidney injury (Bi et al, 2018), chronic glomerulonephritis (Yu et al, 2020), arthritis (Hu et al, 2019), and acute enteritis (Sha et al, 2019). In addition, modulation by rhein of gut microbiota and purine metabolism in the intestine to alleviate chronic colitis (Wu, Wei, et al, 2020), and protection of the epithelial barrier in cytokine‐stimulated intestinal epithelial cells have also been demonstrated (Zhuang, Zhong, Zhou, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with chrysophanol and emodin, rhein showed a strong inhibitory effect on renal fibrosis. Although rhein has been widely demonstrated to protect against renal fibrosis ( Zeng et al, 2014 ; Hu et al, 2019 ; He et al, 2020 ; Wu et al, 2020 ; Yu et al, 2020 ), only two previous studies have reported that rhein protected against renal fibrosis by inhibiting the NF-ƙB p65 protein expression ( Liu et al, 2021b ) and lincRNA-COX2/miR-150-5p/STAT1 axis ( Hu et al, 2020b ). Similarly, a number of publications have demonstrated that emodin retarded renal fibrosis by modulating several pathways, such as TGF-β/Smad, TGF-β/BMP-7, PI3K/Akt/GSK-3β, and Bax/caspase-3 signaling pathways ( Jing et al, 2017 ; Ma et al, 2018b ; Yang et al, 2020 ; Liu et al, 2021c ).…”
Section: Discussionmentioning
confidence: 99%